Distinct roles of nucleosome sliding and histone modifications in controlling the fidelity of transcription initiation. Issue 11 (2nd November 2021) - Zhang, Huiming; Lu, Zhaolian; Zhan, Yu; Rodriguez, Judith; Lu, Chen; Xue, Yong; Lin, Zhenguo
ABSTRACT: Regulation of gene expression starts from the transcription initiation. Regulated transcription initiation is critical for generating correct transcripts with proper abundance. The impact of epigenetic control, such as histone modifications and chromatin remodelling, on gene regulation has been extensively investigated, but their specific role in regulating transcription initiation is far from well understood. Here we aimed to better understand the roles of genes involved in histone H3 methylations and chromatin remodelling on the regulation of transcription initiation at a genome-scale using the budding yeast as a study system. We obtained and compared maps of transcription start site (TSS) at single-nucleotide resolution by nAnT-iCAGE for a strain with depletion of MINC (Mot1-Ino80C-Nc2) by Mot1p and Ino80p anchor-away ( Mot1&Ino80AA ) and a strain with loss of histone methylation ( set1Δset2Δdot1Δ ) to their wild-type controls. Our study showed that the depletion of MINC stimulated transcription initiation from many new sites flanking the dominant TSS of genes, while the loss of histone methylation generates more TSSs in the coding region. Moreover, the depletion of MINC led to less confined boundaries of TSS clusters (TCs) and resulted in broader core promoters, and such patterns are not present in the ssdΔ mutant. Our data also exhibits that the MINC has distinctive impacts on TATA-containing and TATA-less promoters. In conclusion, our study shows that MINC is required for accurate identification of bona fide TSSs, particularly in TATA-containing promoters, and histone methylation contributes to the repression of transcription initiation in coding regions.